Catalysis of proline isomerization and molecular chaperone activity in a tug-of-war - Filippo Favretto; David Flores; Jeremy D. Baker; Timo Strohäker; Loren B. Andreas; Laura J. Blair; Stefan Becker; Markus Zweckstetter (Nature Communications, 2020)
Cyclophilin A (CypA) is a peptidylprolyl isomerase that also has chaperone activity and interacts with the intrinsically disordered protein α-Synuclein (aSyn). Here, the authors combine NMR measurements and biochemical experiments to characterise the interplay between the catalysis of proline isomerization and molecular chaperone activity of CypA and find that both activities have opposing effects on aSyn and further show that the that cis/trans isomerization outpowers the holding activity of CypA.